Recovery Capabilities of Rateless Codes on Simulated Turbulent Terrestrial Free Space Optics Channel Model. (22nd August 2013) - Andò, A.; Mangione, S.; Curcio, L.; Stivala, S.; Garbo, G.; Pernice, R.; Busacca, A. C.
Abstract : Free Space Optics (FSO) links are affected by several impairments: optical turbulence, scattering, absorption, and pointing. In particular, atmospheric optical turbulence generates optical power fluctuations at the receiver that can degrade communications with fading events, especially in high data rate links. Innovative solutions require an improvement of FSO link performances, together with testing models and appropriate channel codes. In this paper, we describe a high-resolution time-correlated channel model able to predict random temporal fluctuations of optical signal irradiance caused by optical turbulence. Concerning the same channel, we also report simulation results on the error mitigation performance of Luby Transform, Raptor, and RaptorQ codes.